Effect of the Increase in Vertical Web Member Stiffness on Lateral Buckling Strength of the Pony Steel Bridge - Hidajat Sugihardjo; Moh F. Rosyidi; Budi Suswanto (Institut Teknologi Sepuluh Nopember (ITS), 2025)
In half-through bridge or pony steel bridge, that is a bridge without upper windbracing, strength of the bridge is determined mainly by the lateral bucklingstrength of its upper chord. Buckling strength of this chord is provided by theflexural stiffness of vertical web member, cross beam, and diagonal beam. In orderto improve the stiffness of vertical web member, triangular steel profile that wasquite high was added to the inner side of bridge for reducing the clearance widthin bridge and disturbing traffic or pedestrian. In this research, stiffness of thevertical web member was improved by using the non-prismatic cross section andadding the triangular stiffener as high as the concrete deck. Finite ElementAnalysis for the lateral stiffness of bridge cross section used a 3D element modelwhich has been validated by previous study. This numerical study was conductedto validate the Engesser theory for determining the lateral elastic stiffness fromupper chord. Study shows the result that accuracy of 3D element model isextremely high, compared with analytic method. Lateral elastic stiffness of bridgein general increased along with the stiffness of vertical web member. However, itcan be concluded that effect on the capability of lateral buckling in upper chordwas not too significant, as a consequence of the increase in stiffness of verticalweb member. Critical lateral buckling occurred in an inelastic range, in which thecritical inelastic buckling stress was determined using small tangent modulus asalternative of modulus of elasticity.